Effect of iRoot SP and mineral trioxide aggregate (MTA) on the viability and polarization of macrophages. (August 2017) - Zhu, Xiaodan; Yuan, Zhenglin; Yan, Ping; Li, Yuhong; Jiang, Han; Huang, Shengfu
Highlights: MTA and iRoot SP have good biocompatibility with 264.7 macrophages. MTA and iRoot SP were found to promote the gene expression of several cytokines, including IL-1β, TNF-α, IL-10 and IL-12p40. MTA and iRoot SP induced both M1 and M2 polarization of the RAW 264.7 macrophages. Abstract: Objective: This study was performed to investigate the effect of iRoot SP and mineral trioxide aggregate (MTA) on the viability and polarization of macrophages. Methods: The effect of iRoot SP and MTA on the viability of RAW 264.7 macrophages was tested using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay after 1 and 2 days of culture. The gene expression levels of interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), interleukin 10 (IL-10), interleukin 12p40 (IL-12p40) were measured by quantitative real time polymerase chain reaction (qRT-PCR) after stimulation of the RAW 264.7 macrophages with iRoot SP and MTA. The expression levels of CD11c and CD206 in RAW 264.7 macrophages were examined by immunofluorescence and flow cytometry after stimulation with iRoot SP and MTA. The data were analyzed by one-way analysis of variance and the Tukey test. Results: Both iRoot SP and MTA were non-toxic to the RAW 264.7 macrophages. The use of iRoot SP and MTA increased the expression of IL-1β, TNF-α, IL-10, IL-12p40 on the first day of culture and could promote macrophage M1 and M2 polarization. Conclusions: MTA and iRoot SP have good biocompatibility with macrophages, and they induced both M1 and M2 polarization of the RAW 264.7 macrophages.